On the Night Before Kindergarten - Wells, Rosemary (New York, New York : Simon & Schuster Books for Young Readers, 2023)
"The night before he starts kindergarten Milo's dreams are full of worry, but after a fun first day of school, Milo decides that he likes kindergarten!"--
Keywords: First day of school -- Juvenile fiction; Kindergarten -- Juvenile fiction; Schools -- Juvenile fiction; First day of school -- Fiction; Kindergarten -- Fiction; Schools -- Fiction; Picture books